Active deformation to the north of the Altyn Tagh Fault: Constraints on the northward growth of the northern Tibetan Plateau. (15th August 2020) - Yun, Long; Zhang, Jin; Wang, Ju; Yang, Xiaoping; Qu, Junfeng; Zhang, Beihang; Zhao, Heng
Graphical abstract: Highlights: The sinistrally transpressive deformation occurs to the north of the Altyn Tagh fault. The Sanweishan fault is active with a sinistral strike-slip rate up to 0.3 mm/a. The growth of the Sanweishan fault is similar to that of the ATF and is a youthful ATF. Clockwise rotation and eastward movement of blocks occur to the north of ATF. Abstract: Sinistral transpressive deformation occurs in the region north of the Altyn Tagh fault due to the Indo-Eurasian collision. In this region, several late Cenozoic faults have developed, and the Sanweishan fault is the key feature with clear landforms. In this study, slip rate measurements combined with several dating methods imply that the Sanweishan fault has been active with sinistral strike-slip rates of 0.33 ± 0.04 mm/a since 14 ka BP and 0.28 ± 0.03 mm/a since 20 ka BP, which are more than an order of magnitude smaller than that of the ATF to the south. The horizontal displacements are 1.7–5.5 m in the eastern segment and 25.0–76.0 m in the middle and western segments of the Sanweishan fault. The increment of horizontal displacement along the main Sanweishan fault is 3.0–4.0 m between paleoearthquakes, and the magnitude of the latest paleoearthquake on the middle and eastern segments of the fault is up to M = 7.2–7.5. The whole length of the Sanweishan fault is 360 km or longer, which include active faults in the Yangguan and Danghe Reservoirs in the west. More components of thrusting occur on the western and eastern segments of the Sanweishan fault. The growth of the Sanweishan fault is similar to that of the ATF, but the former fault is younger, and its slip rate is much smaller. The differential slip rates on the Sanweishan fault and ATF may result in the clockwise rotation and eastward movement of the intervening block, which compresses regions to the northeast.